Collective choices under ambiguity - M. Vittoria Levati; Stefan Napel; Ivan Soraperra (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
We investigate experimentally whether collective choice matters for individual attitudes to ambiguity. We consider a two-urn Ellsberg experiment: one urn offers a 45% chance of winning a fixed monetary prize, the other an ambiguous chance. Participants choose either individually or in groups of three. Group decision rules vary. In one treatment the collective choice is taken by majority; in another it is dictated by two group members; in the third it is dictated by a single group member. We observe high proportions of ambiguity averse choices in both individual and collective decision making. Although a majority of participants display consistent ambiguity attitudes across their decisions, collective choice tends to foster ambiguity aversion, especially if the decision rule assigns asymmetric responsibilities to group members. Previous participation in laboratory experiments may mitigate this.
Keywords: C91; C92; D71; D81; 330; ambiguity aversion; dictatorship; majority voting